INOVASI INTEGRASI BISNIS BERBASIS GOTONG ROYONG PADA KELOMPOK BUDI DAYA IKAN AIR TAWAR “BANYU PINARUH” KABUPATEN TABANAN - Made Kembar Sri Budhi; Putu Yudy Wijaya; I Putu Fery Karyada; Kadek Oki Sanjaya (Jurnal Abdi Insani, 2022)
The freshwater fish farming group "Banyu Pinaruh" located in Rejasa Village, Penebel, Tabanan Regency, Bali Province is one of the businesses that was negatively affected by the COVID-19 pandemic. The problems faced include business managerial aspects (bookkeeping), group development development, capital, and aspects of marketing/distribution technology. The purpose of this service activity is to increase the competitiveness of partners by efforts to overcome partner problems, which involve business managerial aspects, aspects of group development development, aspects of capital, and aspects of marketing/distribution technology. This service activity is carried out by applying technology (IT) in managing partner businesses. The implementation stages carried out are: identification, system design, system creation, system operational assistance, and system implementation. Training activities are also provided to provide understanding for partners, as well as assistance aimed at ensuring partners are able to manage independently so that the results of the activities are sustainable. The implementation team of this service activity was carried out through education through lectures on group management in a professional manner. The team has also prepared a managerial application (bookkeeping) that can be used by partners in financial records. In addition, a website called Direcs has also been prepared, which has a marketplace and crowdfunding menu for the capital aspect. Partners have been given training and assistance to be able to use the application and website in a sustainable manner. The existence of this community empowerment program has had an impact on increasing business capacity for partners, such as increasing the number of productive ponds, frequency and number of harvests, as well as turnover and profits obtained by partners. Activities are carried out through providing education, training, and mentoring for partners. In addition to lectures on professional business management, managerial applications (bookkeeping) and websites (marketplace and crowdfunding) are prepared which are then used by partners.